2003
DOI: 10.1364/ol.28.000387
|View full text |Cite
|
Sign up to set email alerts
|

Two-axis bend measurement with Bragg gratings in multicore optical fiber

Abstract: This version is available at https://strathprints.strath.ac.uk/42768/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
124
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(130 citation statements)
references
References 11 publications
0
124
2
Order By: Relevance
“…The thermal effect can be compensated using differential strain configurations in which the thermal effect is common to all considered gratings (Flockhart et al 2003). Both the local Bragg wavelength shifts (i.e.…”
Section: Fbg Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal effect can be compensated using differential strain configurations in which the thermal effect is common to all considered gratings (Flockhart et al 2003). Both the local Bragg wavelength shifts (i.e.…”
Section: Fbg Sensingmentioning
confidence: 99%
“…This requires the gratings to be located outside the neutral (bending) axis of a cantilever structure. Examples of FBG curvature sensors (Flockhart et al 2003) and accelerometers (Fender et al 2007) have also been developed using multicore optical fibres with multiple cores positioned away from the neutral axis.…”
Section: Introductionmentioning
confidence: 99%
“…The fibre cross-section is illustrated in Figure 1 . The circular cross-section is particularly important for fibre handling, and we have observed that higher quality cleaves can be obtained using this fibre in contrast to other (noncircular) multicore fibres that we have tested previously [7]. This has allowed us to make low-loss (<1dB) splices between lengths of multicore fibre using a Vytran splicer with fibre rotation and alignment facility.…”
Section: Writing Gratings In Multicore Fibrementioning
confidence: 99%
“…This has allowed us to make low-loss (<1dB) splices between lengths of multicore fibre using a Vytran splicer with fibre rotation and alignment facility. The intrinsic photosensitivity of this multicore fibre permits UV-inscription of the FBG structures in the cores without hydrogenation of the fibre -an essential treatment for grating fabrication in standard telecom and the non-circular fourcore fibres that we have used in previous work [7]. We have produced high-efficiency FBGs in this multicore fibre using the standard phase mask scanning technique [8] and a frequency doubled Ar laser with a 95mW output at 244nm.…”
Section: Writing Gratings In Multicore Fibrementioning
confidence: 99%
See 1 more Smart Citation